Predictors of appropriate shock after generator replacement in patients with an implantable cardioverter defibrillator. Issue 5 (16th April 2021) - Arcinas, Liane A.; Chew, Derek S.; Seifer, Colette M.; Baranchuk, Adrian; Supel, Izabella; Exner, Derek V.; Boles, Usama; McIntyre, William F.
Abstract: Background: Implantable cardioverter defibrillators (ICDs) are indicated for the primary prevention of sudden cardiac death in patients with reduced left ventricular ejection fraction (LVEF). The ongoing risk/benefit profile of an ICD at generator replacement is unknown. This study aimed to identify predictors of appropriate ICD shocks and therapies after first ICD generator replacement, and its procedure‐related complications. Methods: We conducted a multicenter, retrospective cohort study including patients with primary prevention ICDs who underwent generator replacement between April 2005 and July 2015 at three Canadian centers. The primary and secondary outcomes were appropriate ICD shock and any appropriate ICD therapy, respectively. Procedure‐related complication rates were also reported. Results: Of the 219 patients in the cohort, 61 (28%) experienced an appropriate shock while 40 (18%) experienced appropriate antitachycardia pacing over a median follow up of 2.2 years. Independent predictors of appropriate ICD shocks included: LVEF at time of replacement (adjusted odds ratio [OR] 0.4 per 10% increase in LVEF, P  < .001), a history of appropriate ICD shocks prior to replacement (OR 4.9, P  < .001), and a history of inappropriate ICD shocks (OR 4.2, 95%, P  < .002). Similar predictors were identified for the secondary outcome of any appropriate ICD therapy. Device‐related complications were reported in 25 (11%) patients, with 1 (0.5%) resulting in death, 14 (6.3%) requiring site re‐operation, and 6 (2.7%) requiring cardiac surgical management. Conclusion: Not all primary prevention ICD patients undergoing generator replacement will require appropriate device therapies afterwards. Generator replacement is associated with several risks that should be weighed against its anticipated benefit. A comprehensive assessment of the risk‐benefit profile of patients undergoing generator replacement is warranted.